ANALYSIS OF STRATEGIES TO INCREASE THE COMPETITIVENESS OF INDONESIAN PRODUCT EXPORTS IN THE GLOBAL MARKET: CASE STUDY IN THE CREATIVE AND FASHION INDUSTRY - shihab, habib; Prastiwi, Lustina Fajar (Jurnal Ilmu Ekonomi dan Bisnis, 2024)
Abstract: The creative and fashion industries in Indonesia have great potential to contribute to increasing national exports. However, the competitiveness of Indonesian products in the global market still faces various challenges, such as competition from competitors, compliance with international quality standards, and passive marketing strategies. The aim of this research is to explore and understand in depth the strategies implemented by industrial export players. Indonesian creative and fashion in increasing the competitiveness of their product exports in the global market so that they can make a positive contribution to national economic development and encourage sustainable economic growth. This research uses a qualitative approach with case study and observation methods. Research data was taken secondary by searching from related literature sources. In this case study, researchers analyzed several strategies which were then implemented to increase the competitiveness of exports of Indonesian creative and fashion industry products in the global market. Keywords: Export, Creative Industry, Fashion